MEMBANGUN EKOSISTEM KEWIRAUSAHAAN UNTUK USAHA MIKRO DAN KECIL DI INDONESIA: SEBUAH TINJAUAN LITERATUR - Armando Haratua, Chandra Wijaya (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Building Entrepreneurial Ecosystems for Micro and Small Businesses in Indone-sia: A Literature Review. Micro and small businesses play a strategic role in reducing poverty and unemployment in Indonesia. Despite its important role, the ratio of micro and small businesses in Indonesia is still inadequate to sustain the national economy. There are various problems experienced by micro and small businesses, such as capital, human resources, regulations, government support, social culture, and lack of support from educational institutions. These problems are part of the entrepreneurial ecosystem, which is a theoretical approach to entrepreneurship development. The entrepreneurial ecosystem is composed of culture, policy, finance, human resources, markets, institutions and infrastructure that must be linked and coordinated both formal and informal. The entrepreneurial ecosystem in Indonesia needs to be developed into an ecosystem that supports each other among the actors and the factors within it in order to have a positive influence on micro and small businesses. Research on entrepreneurial ecosystems in Indonesia needs to be improved and developed in order to provide a conceptual description of the entrepreneurial ecosystem that matches the character of entrepreneurship in Indonesia.